O avanço das tecnologias digitais na educação escolar e suas implicações político pedagógicas - Oliveira, Geanandréia Zanoni de (2023)
Technologies accompany the process of humanity's development and play an essential role in mediating between humankind and nature and in satisfying their needs. They are the result of objective reality; however, due to the production mode in which they are inserted, they change their form and acquire connotations that make their neutrality impossible. Hence, one can argue that technologies fulfill a function according to the production mode's needs. They fulfill a positive aspect, reducing human suffering, promoting the enjoyment and socialization of production and social and human development, and providing solutions for diseases and other ills that afflict us. However, they also can promote the opposite of this, depleting natural resources, polluting and causing environmental imbalance, taking away workers' jobs, determining an increasingly faster pace of production, and establishing a relationship of dependence between man and technology, which ends up increasingly expropriating him. The high degree of technological development present today is causing a change in the production of the material base and the reorganization of the social life of individuals. When dealing with the advance of digital technologies in school education and its political and pedagogical implications, one question arises: what are the consequences of this technological advance on Brazilian public education in general and public schools in particular? In order to answer this question, we conducted bibliographic research, which provided the theoretical framework to discuss the role of technologies throughout history, conceptualizing what technology is and what its social function is, linked to the historical relationship between labor and education, as the result of materialized human intellectual work. We seek to understand the role of technologies in the current stage of capitalist development, which combines the high concentration of capital and the private appropriation of production and property with a high degree of technological development. Also, this work aims to understand the consequences of new digital technologies on public schools, their impact on labor relations within the capitalist production mode, and to point out the need to socialize them. For this, we sought to verify how they could be used to enhance education and aim at the integral formation of students and their socialization due to overcoming the current production mode so that they can fulfill their social function, which is to guarantee the whole human, social, and collective development.